Study of the structural and morphological characteristics of the CdxTeyOz nanocomposite obtained on the surface of the CdS/ZnO heterostructure by the SILAR method - Suchikova, Yana; Kovachov, Sergii; Bohdanov, Ihor; Karipbaev, Zhakyp T.; Pankratov, Vladimir; Popov, Anatoli I. (Springer, 2023)
CdxTeyOz nanocomposite films were grown by the SILAR method on the CdS/ZnO surface during cyclic processing in precursor solutions followed by removal of excess reagent from the surface of the substrate by washing in hydrogen peroxide. To stabilise the surface states and saturate with oxygen, the surface was annealed in a diffusion furnace. XRD, RAMAN, and SEM analyses were used to analyse the phase composition, structural, and substructural parameters. The nanocomposite film consists of different types of oxides, namely trigonal TeO3, Monoclinic TeO4 and CdTe3O8, orthorhombic TeO2 and CdTeO3. The formation of films is explained using the Volmer–Weber growth mechanism. SEM analysis of the formed nanocomposite showed the presence of nanometer-scale globules. Partial amorphization of the heterostructure occurs due to the presence of nanometer-sized particles. --//-- This is an open access article: Suchikova, Y., Kovachov, S., Bohdanov, I. et al. Study of the structural and morphological characteristics of the CdxTeyOz nanocomposite obtained on the surface of the CdS/ZnO heterostructure by the SILAR method. Appl. Phys. A 129, 499 (2023). https://doi.org/10.1007/s00339-023-06776-x published under the CC BY licence.
This work was supported by the Government of Ukraine (Ministry of Education and Science of Ukraine via project 0122U000129 and 0121U10942). In addition, the research of A.I.P was partly supported by the RADON project (GA 872494) within the H2020-MSCA-RISE-2019 call and COST Action CA20129 “Multiscale Irradiation and Chemistry Driven Processes and Related Technologies” (MultIChem). A.I.P. also thanks to the Institute of Solid-State Physics, University of Latvia. ISSP UL as the Center of Excellence is supported through the Framework Program for European universities, Union Horizon 2020, H2020-WIDESPREAD-01-2016-2017-TeamingPhase2, under Grant Agreement No. 739508, CAMART2 project.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; SILAR method; Cadmium-tellurium oxides; Electrolyte; Nanocomposite; Heterostructure